Pengaruh Terapi Kognitif Restrukturisasi terhadap Penurunan Skor Depresi pada Pasien Gangguan Jiwa - Astuti, Wening Marsudi; Sumarwati, Made; Setyono, Tulus (Jurusan Keperawatan FIKES UNSOED, 2010)
Depression disorder is the most kind of mental disorder. During this periode the therapy which done at sakura room of Banyumas public hospital for mental disorder patients is ECT, phycofarmaca and the aerobic exercise. The cognitive therapy is applied to depression patients which has more advantages. It is cheaper and more practical. This study aimed to examine the effect of cognitive therapy restructuritation in decreasing depression score of the mental disorder patient of Banyumas public hospital. This study used quasi experimental with series experiment or time series design. Total sampling was applied. A total of twenty nine depression patients in Sakura room were studied. Dependent t-test was applied to analize the data. The mayority of the age respondent between 16-24 years old. The male was fewer than female. The single status was more than the marriage status. The mayority of education were junior high school and the minority are DIII. The average of depression score after treated by cognitive therapy: once cognitive restructuritation was be decrease and after twice treated by this therapy more be decrease again. The cognitive therapy : cognitive restructuritation has a significant effect to decrease depression score of the mental disorder patients of Banyumas public hospital. Two times cognitive therapy was more effective than once therapy. The cognitive therapy : cognitive restructuritation has a significant effect to decrease depression score of mental disorder patients.